Differences in exosome populations in human breast milk in relation to allergic sensitization and lifestyle. Issue 4 (15th January 2014) - Torregrosa Paredes, P.; Gutzeit, C.; Johansson, S.; Admyre, C.; Stenius, F.; Alm, J.; Scheynius, A.; Gabrielsson, S.
Abstract Background Breast‐feeding has many beneficial effects on the developing immune system of the newborn. Breast milk contains immunoregulatory factors, such as nano‐sized vesicles named exosomes. This study aimed at characterizing breast milk exosomes from human early milk and mature milk and to investigate whether allergic sensitization and an anthroposophic lifestyle could influence the exosome profile. Methods Breast milk was collected from 22 mothers at day 3–8 and from 61 mothers at 2 months postpartum, all part of the ALADDIN birth cohort. Isolated exosomes were captured on anti‐MHC‐class II‐ or anti‐CD63 beads and analyzed by flow cytometry. Exosomal phenotype was related to lifestyle and allergic sensitization of the mothers, and sensitization of the child at 2 years of age. Results We found a higher content of exosomes in early milk compared with mature milk. Early milk exosomes were enriched in HLA‐DR molecules and displayed significantly lower levels of HLA‐ABC compared with those in mature milk. Phenotypically different subpopulations of exosomes were found in mature milk. Significantly lower levels of MUC1 were detected on CD63‐enriched exosomes from sensitized mothers compared with nonsensitized. Furthermore, women with an anthroposophic lifestyle had significantly lower MUC1 expression on their HLA‐DR‐enriched milk exosomes and up‐regulated levels of CD63 on CD63‐enriched exosomes compared with nonanthroposophic mothers. Notably, mothers whose children developed sensitization had an increased amount of HLA‐ABC on their milk exosomes enriched for CD63. Conclusions The phenotype of exosomes in breast milk varies with maternal sensitization and lifestyle, which might influence allergy development in the child.